PP26 Exploring the use of pre-hospital pre-alerts and their impact on patients, ambulance service and emergency department staff: protocol for a mixed methods study. Issue 9 (23rd August 2022) - Sampson, Fiona C; Bell, Fiona; Webster, Peter; Coster, Joanne; O'Hara, Rachael; Goodacre, Steve; Foster, Alexis; Miles, Jamie; Millins, Mark; Pountney, Andrew; Rosser, Andy; Spaight, Robert; et al.
Abstract : Background: Ambulance clinicians use pre-alert calls to inform receiving emergency departments (EDs) of the arrival of a critically unwell patient that will require a specialised response. Little is known about how a decision to pre-alert is made and how this is communicated and acted upon in the receiving ED. Whilst appropriate use of pre-alerts benefits patient care, their overuse carries a risk of harm or opportunity costs. The impact of pre-alerts on ambulance clinicians, ED staff and patients is not currently well understood. Methods: We are conducting a mixed methods study with five inter-related work packages. We will analyse 12 months of routine data from ambulance pre-alerts in three regions to identify factors in the variation of pre-alert use, including pre-hospital decision-making. We will undertake a national online Qualtrics survey of ambulance clinician perspectives and experience of pre-alerts. We will explore the impacts of a pre-alert on staff, ED facilities and the patient using semi-structured interviews with ambulance clinicians, ED staff, patients and carers and undertake non-participant observation of ED pre-alert response. Expected Results: We will describe current pre-alert practice using 12 months' data for 3 Ambulance Services, including volume and types of pre-alerts. We will identify specific conditions or patient groups for whom pre-alerts are most likely to lead to change in clinical practice, or for whom action is unlikely to provide benefit. We will hold a feedback workshop in which we will share and discuss our findings with key stakeholders. Conclusions: Current variation in pre-alert processes, both pre-hospital and in-hospital and the impact on patient care is not understood. The outputs of this study will establish an evidence base to update national guidance for pre-alert practice and identify areas of good pre-alert practice for both ambulance service and Emergency Department staff.